Longitudinal studies of the 18F-FDG kinetics after ipilimumab treatment in metastatic melanoma patients based on dynamic FDG PET/CT - Sachpekidis, Christos; Anwar, Hoda; Winkler, Julia K.; Larribere, Lionel; Haberkorn, Uwe; Hassel, Jessica C.; Dimitrakopoulou-Strauss, Antonia (Cancer immunology immunotherapy, 2018)
BackgroundImmunotherapy has raised the issue of appropriate treatment response evaluation, due to the unique mechanism of action of the immunotherapeutic agents. Aim of this analysis is to evaluate the potential role of quantitative analysis of 2-deoxy-2-(18F)fluoro-d-glucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) data in monitoring of patients with metastatic melanoma undergoing ipilimumab therapy.Methods25 patients with unresectable metastatic melanoma underwent dynamic PET/CT (dPET/CT) of the thorax and upper abdomen as well as static, whole body PET/CT with 18F-FDG before the start of ipilimumab treatment (baseline PET/CT), after two cycles of treatment (interim PET/CT) and at the end of treatment after four cycles (late PET/CT). The evaluation of dPET/CT studies was based on semi-quantitative (standardized uptake value, SUV) calculation as well as quantitative analysis, based on two-tissue compartment modeling and a fractal approach. Patients’ best clinical response, assessed at a mean of 59 weeks, was used as reference.ResultsAccording to their best clinical response, patients were dichotomized in those demonstrating clinical benefit (CB, n = 16 patients) and those demonstrating no clinical benefit (no-CB, n = 9 patients). No statistically significant differences were observed between CB and no-CB regarding either semi-quantitative or quantitative parameters in all scans. On contrary, the application of the recently introduced PET response evaluation criteria for immunotherapy (PERCIMT) led to a correct classification rate of 84% (21/25 patients).ConclusionQuantitative analysis of 18F-FDG PET data does not provide additional information in treatment response evaluation of metastatic melanoma patients receiving ipilimumab. PERCIMT criteria correlated better with clinical response.
Im Titel ist "18" in 18F-FDG hochgestellt
Gesehen am 08.05.2019